Implementasi Green Accounting pada Daerah Rawan Bencana (Studi Fenomenologis pada Pemerintah Daerah Kabupaten Banjarnegara) - Ita Nuryana, Wulan Suci Racmadani, Kuat Waluyo Jati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
The purpose of this research is to know whether Local Government of Banjarnegara Regency: 1) Able to implement green accounting at public institution in Banjarnegara District Government. 2) To increase knowledge in the realm of financial accounting and management on green accounting. Type of research used in this research is qualitative research with descriptive method. Qualitative research procedure with phenomenological approach, after horizonaliting and statement of each participant has been collected into the unit of meaning and written a picture of how the experience occurred, then the results are developed through the overall description of the existing phenomenon so as to find the essence of the phenomenon. The results obtained that the understanding of green accounting implementation in Banjarnegara area is good. This is evident from the results of in-depth interview and observation of the participants already know the procedures regarding the management of disaster emergency response, financial statements on green accounting produced by Local Government Banjarnegara already integrated well and audited by BPKP and appointment of public accounting firm.